Pemanfaatan Limbah Pertanian Sebagai Pakan Total Mixed Ration (TMR) di Ternak Kambing Etawa pada Kandang Kelompok Ternak Aikmual di Kabupaten Lombok Tengah - M. Ridwan Saedi; Muhamad Ali; Muh. Aidil Fitriyan Fadjar Suryadi (Jurnal Pengabdian Masyarakat Sains Indonesia, 2026)
The main problem faced by the Aikmual Livestock Group is the limited availability of quality feed on a sustainable basis, especially during the dry season. This community service activity aims to improve the knowledge and skills of farmers in utilizing agricultural waste as Total Mixed Ration (TMR) feed. The methods used included counseling, practical training (demonstration plots), and mentoring in implementing TMR. The results showed an 85% increase in farmers' understanding based on pre- and post-tests. Farmers were able to formulate TMR based on local waste and apply it to Etawa crossbred goats. The implementation of TMR improved feed palatability and farmer work efficiency.